Spiritual Discourse in the Academy: A Globalized Indigenous Perspective - Ilmi, Ahmed Ali; Adyanga, Francis Akena (Black Studies and Critical Thinking, 2012)
Contents: Francis Akena Adyanga: African Spirituality and the Traditional Justice System: Pedagogical Implications for Education – Elias K. Bongmba: Spirituality: An Intersubjective Practice – Onek C. Adyanga: Response to the Context Theme – Jean-Paul Restoule/Erin Wolfson/Candace Brunette/Christine Smillie/Angela Mashford-Pringle/Maya Chacaby/Gail Russel: Supporting Aboriginal Learners in Post-Secondary Education Institutions in Ontario – Ahmed Ali Ilmi: Claiming the Sacred: Indigenous African Spirituality and Schooling – Neville G. Panthaki: Swaraj, Spirituality, and Saraswati: Conceptualizing Post-Colonial Indian Secular Cosmopolitanism as Identity, and Education – Mary Ashiedu: Spirituality as a Strategy for Survival: An Igbo Perspective – Onek C. Adyanga: Response to the Pedagogy Theme – Theme Three: Discourse – Njoki Nathani Wane: Students’ Spiritual Selves: Implications for Classroom Practices – Erick Fabris: Spirituality and a Mad People's Commons – Natalie McDoom-Slack: The Liberation of Critical Pedagogy: Towards an Understanding of Spirituality and Education – Michael Onyedika Nwalutu: Dispiriting the Spiritual in Classroom Education: Critiquing Spirituality as a Tool for Transformative Education in 21st-Century Academe – Margarita Simon Guillory: The Creative Individual: Identity Construction and Individuality in African American Spirituality – Mindy Lee: Chinese Spirituality: Implications for Western Educators – Bradley D. Rowe: American Emerson: A Response to the Discourse Theme – Njoki Nathani Wane/Ahmed Ali Ilmi/Francis Akena Adyanga: Conclusion: An Invitation to Continuous Dialogue on Indigenous Spiritual Ways of Knowing.